Unmet Spiritual Needs, Spiritual Wellbeing and Support Satisfaction of End-of-Life Patients: Findings from a Spiritual and Existential Care Training Program (SpECi) for Health Care Practitioners within Inpatient Geriatric Care, Palliative Care Units and Hospices - Büssing, Arndt (Journal of religion and health, 2025)
The outcomes of a 40-h Spiritual/Existential Care training program (SpECi) for healthcare professionals on their patients' treatment satisfaction (n = 774) were evaluated. Most patients felt supported in their spiritual needs by the staff (79-81%). This satisfaction was highest in hospices and palliative care units (Eta2 = .065, p < .001). Regression analyses revealed that satisfaction with spiritual needs support was predicted by therapeutic staff support, treatment place, and support from pastoral care providers (R2 = .17). The prominent role of healthcare practitioners with their specific competencies and spiritual care ideals is crucial for patients' support satisfaction which was higher for family and staff than to pastoral care providers.